Exploring targeted pulmonary delivery for treatment of lung cancer - Goel, Amit; Baboota, Sanjula; K Sahni, Jasjeet; Ali, Javed (International Journal of Pharmaceutical Investigation, 2013)
Lung cancer is the most malignant cancer today. The treatment of lung cancer continues to be a challenge for oncologists. The direct delivery of chemotherapeutic agents to the lungs could represent a novel therapeutic approach for patients with pulmonary metastases. The large alveolar surface area, the low thickness of the epithelial barrier, and an extensive vascularization make the pulmonary route an ideal route for administration of oncolytics. This paper reviews the research performed over the last and current decades on the delivery of various oncolytics for pulmonary delivery for the treatment of lung cancer. Inhaled drug delivery devices in cancer therapy are also discussed in the present manuscript.
Keywords: Lung cancer; oncolytics; pulmonary route